Basic economics - Sowell, Thomas (New York, NY 10107 Basic Books, 2015)
Basic Economics is a citizen's guide to economics, written for those who want to understand how the economy works but have no interest in jargon or equations.
Index: p.659-689
Keywords: Quản trị kinh doanh